2019
DOI: 10.1002/csr.1733
|View full text |Cite
|
Sign up to set email alerts
|

Are cultural values sufficient to improve stakeholder engagement human and labour rights issues?

Abstract: The complexity of the business world and current business models has motivated an increasing number of companies to disclose corporate information through sustainability reports. This reporting and stakeholders engagement may bring shared value to business and society in general although working towards sustainable development goals. This work adopts a new analytical approach by determining the global reporting initiative indicators related to labour practices and decent work, human rights, society, and produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 56 publications
(64 citation statements)
references
References 155 publications
4
36
0
3
Order By: Relevance
“…Robbins () states that the cultural dimensions of Hofstede () are a frame of reference for differentiating national cultures. This reference is originally integrated into four dimensions (individualism/collectivism, masculinity/femininity, tolerance/evasion of uncertainty, and power distance); and from there, it becomes a model of culture (Hofstede, ; Hofstede & Hofstede, ) widely used in the field of CSR (Christie, Kwon, Stoeberl, & Baumhart, ; Cubilla‐Montilla, Nieto‐Librero, Galindo‐Villardón, Vicente Galindo, & García‐Sánchez, ; Gallego‐Álvarez & Ortas, ; I. M. García‐Sánchez et al, 2013; Ho, Wang, & Vitell, ; Husted, ; Newson & Deegan, ; Orij, ; Park, Russell, & Lee, ; Peng, Dashdeleg, & Chih, ; Vachon, ; Van der Laan Smith, Adhikari, & Tondkar, ; Vitell, Paolillo, & Thomas, ; Waldman et al, ).…”
Section: Environmental Information and Isomorphismmentioning
confidence: 99%
“…Robbins () states that the cultural dimensions of Hofstede () are a frame of reference for differentiating national cultures. This reference is originally integrated into four dimensions (individualism/collectivism, masculinity/femininity, tolerance/evasion of uncertainty, and power distance); and from there, it becomes a model of culture (Hofstede, ; Hofstede & Hofstede, ) widely used in the field of CSR (Christie, Kwon, Stoeberl, & Baumhart, ; Cubilla‐Montilla, Nieto‐Librero, Galindo‐Villardón, Vicente Galindo, & García‐Sánchez, ; Gallego‐Álvarez & Ortas, ; I. M. García‐Sánchez et al, 2013; Ho, Wang, & Vitell, ; Husted, ; Newson & Deegan, ; Orij, ; Park, Russell, & Lee, ; Peng, Dashdeleg, & Chih, ; Vachon, ; Van der Laan Smith, Adhikari, & Tondkar, ; Vitell, Paolillo, & Thomas, ; Waldman et al, ).…”
Section: Environmental Information and Isomorphismmentioning
confidence: 99%
“…In practice, however, several studies have revealed the existence of information deficiencies (Asif, Searcy, dos Santos, & Kensah, 2013;Mio, 2010;Moseñe, Burritt, Sanagustín, Moneva, & Tingey-Holyoak, 2013;Rodrigue, 2014) that hinder decision-making by the different stakeholders (Fonseca, McAllister, & Fitzpatrick, 2012;O'Dwyer, Unerman, & Hession, 2005). Among other weaknesses, the fact that the information disclosed is minimal, of limited effectiveness and credibility, and rarely comparable, all limits corporate transparency (Amini, Bienstock, & Narcum, 2018;Boiral & Henri, 2017; Cubilla-Montilla, Nieto-Librero, Galindo-Villardón, Vicente Galindo, & Garcia-Sanchez, 2019;Hossain, Momin, Rowe, & Quaddus, 2017;Mio, 2010). In addition, it has been empirically demonstrated that the relevance of the NFI disclosed is associated with the existence of firms' incentives.…”
Section: Introductionmentioning
confidence: 99%
“…This method has been applied by Carrasco et al [32] in hydrology; Cubilla-Montilla et al [33], Amor-Esteban et al [34] and García-Sánchez et al [35] in the context of corporate social responsibility; Castellanos-Martín et al [36] in breast cancer research; Gallego-Alvarez et al [37] and Tejedor-Flores [38] to analyse sustainability; Nieto-Librero et al [39] in geochemical studies; Hernández et al [40] to study bioactive compounds in agriculture; Mendes et al [30] in environmental science; García-Talegón [41], in geology, and; Orfao et al [42] in immunology.…”
Section: Methodology I: Hj-biplot Methodsmentioning
confidence: 99%